The PB2 Polymerase Host Adaptation Substitutions Prime Avian Indonesia Sub Clade 2.1 H5N1 Viruses for Infecting Humans - Wang, Pui (Viruses, 2019)
Significantly higher numbers of human infections with H5N1 virus have occurred in Indonesia and Egypt, compared with other affected areas, and it is speculated that there are specific viral factors for human infection with avian H5N1 viruses in these locations. We previously showed PB2-K526R is present in 80% of Indonesian H5N1 human isolates, which lack the more common PB2-E627K substitution. Testing the hypothesis that this mutation may prime avian H5N1 virus for human infection, we showed that: (1) K526R is rarely found in avian influenza viruses but was identified in H5N1 viruses 2–3 years after the virus emerged in Indonesia, coincident with the emergence of H5N1 human infections in Indonesia; (2) K526R is required for efficient replication of Indonesia H5N1 virus in mammalian cells in vitro and in vivo and reverse substitution to 526K in human isolates abolishes this ability; (3) Indonesian H5N1 virus, which contains K526R-PB2, is stable and does not further acquire E627K following replication in infected mice; and (4) virus containing K526R-PB2 shows no fitness deficit in avian species. These findings illustrate an important mechanism in which a host adaptive mutation that predisposes avian H5N1 virus towards infecting humans has arisen with the virus becoming prevalent in avian species prior to human infections occurring. A similar mechanism is observed in the Qinghai-lineage H5N1 viruses that have caused many human cases in Egypt; here, E627K predisposes towards human infections. Surveillance should focus on the detection of adaptation markers in avian strains that prime for human infection.